1999
DOI: 10.1590/s0100-879x1999000900002
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic DNA damage induced by phycocyanin and its repair in Saccharomyces cerevisiae

Abstract: In the present study, we analyzed DNA damage induced by phycocyanin (PHY) in the presence of visible light (VL) using a set of repair endonucleases purified from Escherichia coli. We demonstrated that the profile of DNA damage induced by PHY is clearly different from that induced by molecules that exert deleterious effects on DNA involving solely singlet oxygen as reactive species. Most of PHY-induced lesions are single strand breaks and, to a lesser extent, base oxidized sites, which are recognized by Nth, Nf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 33 publications
(60 reference statements)
1
4
0
1
Order By: Relevance
“…Apoptotic activity, however, is evident only for higher protein concentrations (>20 μM) and longer incubation times of the cells with the protein (>24h). The trends in DNA damage, induced by C-PC, were found quite similar to those, induced by ionizing radiation or by hydrogen peroxide in the presence of transition metals (Epe, 1995;Padula & Boiteaux, 1999). Notably, for subjects with low cumulative doses of IR and for those from the control group, we registered higher levels of unrepaired DNA lesions both in cells, treated with C-PC and in those, irradiated with 2 Gy.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Apoptotic activity, however, is evident only for higher protein concentrations (>20 μM) and longer incubation times of the cells with the protein (>24h). The trends in DNA damage, induced by C-PC, were found quite similar to those, induced by ionizing radiation or by hydrogen peroxide in the presence of transition metals (Epe, 1995;Padula & Boiteaux, 1999). Notably, for subjects with low cumulative doses of IR and for those from the control group, we registered higher levels of unrepaired DNA lesions both in cells, treated with C-PC and in those, irradiated with 2 Gy.…”
Section: Discussionsupporting
confidence: 76%
“…It seems that the biliprotein selectively improved the DNA repair capacity of the individuals with higher radiosensitivity, which could be of particular interest for the radio-protection of high-risk subgroups of the population and workers. The toxic effect of C-PC, registered in this study, is probably linked to the photosensitizing properties of the protein (Padula & Boiteaux, 1999;Zhang et al, 1999;Paul et al, 2006). It has been shown that visible light, absorbed by the tetrapyrrolic chromophores of phycobiliproteins, can generate reactivate oxygen species (ROS), such as hydroxyl radical and singlet oxygen, which induce oxidative damage to DNA.…”
Section: Discussionmentioning
confidence: 60%
“…Les phycobiliprotéines (phycocyanine de spiruline et phycoerythrine des algues rouges) possèdent par ailleurs des propriétés antioxydantes qui pourraient être mises à profit dans la prévention ou le traitement de maladies dégénératives : certaines formes de cancer, maladies cardiovasculaires ou ophtalmiques liées au stress oxydatif [10,19,20].…”
Section: Proté Inesunclassified
“…Under stress conditions such as high intensity of light, the rate of ROS formation is beyond the quenching capacity of the antioxidant defense systems. The unquenched ROS, particularly singlet oxygen and hydroxyl radicals that are some of the strongest oxidizing agents and can nonselectively attack literally all biomolecules they encounter, are not only highly oxidative to cellular components like DNA , proteins and membrane lipids , but can also suppress the synthesis de novo of proteins, particularly the elongation step of translation in D1 protein synthesis that is essential to the repair of the photodamaged PSII . Superoxide anions and hydrogen peroxide are much less reactive; however, superoxide can be converted by superoxide dismutases (SODs) into hydrogen peroxide, which can produce the highly toxic hydroxyl radicals via the Fenton reaction: (H 2 O 2 + Fe 2+ → OH − + ·OH + Fe 3+ ).…”
Section: Introductionmentioning
confidence: 99%